Scrutinizing the Application of Saline Endophyte to Enhance Salt Tolerance in Rice and Maize Plants - Siddiqui, Zamin Shaheed; Wei, Xiangying; Umar, Muhammad; Abideen, Zainul; Zulfiqar, Faisal; Chen, Jianjun; Hanif, Asma; Dawar, Shahnaz; Dias, Daniel Anthony; Yasmeen, Roomana (Frontiers in Plant Science, 2022)
The present study aimed to witness the plant–microbe interaction associated with salt tolerance in crops. We isolated the endophytic microbe from the root zone of halophytic grass. Later, the salt tolerance of the endophyte was tested in the saline medium and was identified using nucleotide sequencing (GenBank under the accession numbers: SUB9030920AH1_AHK_ITS1MW570850: SUB9030920AH1_AHK_ITS4MW570851). Rice and maize seeds were coated with identified endophyte Aspergillus terreus and were sown in separate plastic pots. Later 21-day-old seedlings were subjected to three NaCl concentrations, including 50, 100, and 150 mM salt stress. Under saline conditions, A. terreus showed a substantial increase in growth, biomass, relative water content, oxidative balance, and photochemical efficiency of rice and maize plants. The data reflected that the stimulation of gibberellic acid (GA) in treated leaves may be the main reason for the upregulation of photosynthesis and the antioxidant defense cascade. The data also depict the downregulation of oxidative damage markers malondialdehyde, hydrogen peroxide in rice and maize plants. Conclusively, salt-tolerant endophytic fungus A. terreus explicitly displayed the positive plant–microbe interaction by developing salt tolerance in rice and maize plants. Salt tolerance by endophytic fungus coincides with the enhanced GA concentration, which illustrated the stimulated physiological mechanism and gene in response to the extreme environmental crisis, resulting in improved crop productivity.